Fortnight (JSTOR)
Fortnight magazine has been providing incisive commentary on all aspects of life in Northern Ireland since 1970. It is the North's longest running independent publication.With a stream of award-winning regional and national journalists attached to it, Fortnight has been able to comment freely and without prejudice on politics, arts and culture.
Keywords: Irish Studies